Blue Black Permanent - Tait, Margaret; Scott, Alex; Imrie, Celia; Shepherd, Jack; Stevenson, Gerda (bfi, 2019)
This haunting and magical film moves between Edinburgh and Orkney as it tells of a woman's attempts to come to terms with her mother's death through her childhood memories. Filled with flashbacks and dream sequences, it's also a film about islander's relationships with the ever-present sea. Margaret Tait's only feature-length film, from her own screenplay, was produced by the BFI in 1992 and was the first Scottish feature film directed by a woman. [Cover]